(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Road transport plays an important role in routine transportation. This paper describes the tie down methodology for transportation container for safe transportation conditions. The methodology adopted for safe transportation conditions comprises of applying known acceleration inputs (varying frequencies) to the given container and correlating the response on virtual simulation model using FEA software. The required input for FEA are taken from Indian road conditions includes accelerations in lateral, longitudinal and vertical directions on the transportation container. The multi-axis simulation table (MAST) is used for determination of acceleration factors through experimentally, using low frequency excitation signals which are generally associated with transport vehicles. These obtained results are compared with FEA results in order to develop methodology for prediction of acceleration factors on transportation container. The developed methodology has been successfully tested on taking an industrial component and found to be reasonable. The same can be used for prediction of dynamic behaviour of industrial component